Learning English in a Third Space? Malay Students in an English-Speaking University in Malaysia - Abdul Wahid, Mohd Ridwan; Pilus, Zahariah (Universiti Putra Malaysia Press, 2017)
It has been suggested that the use of English among Malays is constrained by the intertwining of ethnic identity, religion and native language. This study investigated the possibility of a ‘third space’ (Bhabha, 1994) for a group of Malay-speaking English majors in an English-medium university in Malaysia. Using Norton’s (2013) identity approach to second language acquisition, it found that the participants’ identities as ethnic Malays and Malay-English speaking bilingual were often conflicted as the broader community was disinclined to use English. Despite high motivation levels, dominance of the Malay language curtailed the participants’ investment in English to a great extent. The third space, when available, was confined to sites that were associated with their formal learning of English.